Cendrawasih Bird Optimization Algorithm : A nature-inspired metaheuristic - Widi Aribowo; Laith Abualigah; Diego Oliva; Abeer Aljohani; Aliyu Sabo (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2026)
This study proposes a new metaheuristic algorithm named Cendrawasih Bird Optimization Algorithm (COA), inspired by the natural behavior of Cendrawasih birds—an endemic species of Indonesia. COA mimics the main behavior of the birds, namely exploration and exploitation, to create a balance between global exploration and local exploitation capabilities in solving various optimization problems. This algorithm is mathematically modeled and evaluated using 23 benchmark functions from CEC 2017, and its performance is compared against eight state-of-the-art metaheuristic algorithms. The results of numerical experiments, convergence analysis, and statistical tests show that COA has competitive performance, especially in terms of stability and consistency on unimodal and multimodal functions. Overall, COA is proven to be a reliable, robust, and efficient optimization tool with broad application potential in various engineering and scientific fields.